Use of the MNCD Classification to Monitor Clinical Stage and Response to Levodopa-Entacapone-Carbidopa Intestinal Gel Infusion in Advanced Parkinson’s Disease - Diego Santos-García; Lydia López-Manzanares; Inés Muro; Pablo Lorenzo-Barreto; Elena Casas Peña; Rocío García-Ramos; Tamara Fernández Valle; Carlos Morata-Martínez; Raquel Baviera-Muñoz; Irene Martínez-Torres; María Álvarez-Sauco; Déborah Alonso-Modino; et al. (Brain Sciences)
Background and objective: Staging Parkinson’s disease (PD) with a novel simple classification called MNCD, based on four axes (Motor; Non-motor; Cognition; Dependency) and five stages, correlated with disease severity, patients’ quality of life and caregivers’ strain and burden. Our aim was to apply the MNCD classification in advanced PD patients treated with device-aided therapy (DAT). Patients and Methods: A multicenter observational retrospective study of the first patients to start the levodopa-entacapone-carbidopa intestinal gel (LECIG) in Spain was performed (LECIPARK study). The MNCD total score (from 0 to 12) and MNCD stages (from 1 to 5) were collected by the neurologist at V0 (before starting LECIG) and V2 (follow-up visit). Wilcoxon’s signed rank and Marginal Homogeneity tests were applied to compare changes from V0 to V2. Results: Sixty-seven PD patients (58.2% males; 69.9 ± 9.3 years old) with a mean disease duration of 14.4 ± 6.5 years were included. The mean treatment duration (V2) was 172.9 ± 105.2 days. At V0, patients were classified as in stage 2 (35.8%), 3 (46.3%) or 4 (17.9%). The frequency of patients in stage 4 decreased to 9% at V2 (p = 0.001). The MNCD total score decreased from 6.27 ± 1.94 at V0 to 5.21 ± 2.23 (p < 0.0001). From V0 to V2, the motor (M; p < 0.0001) and non-motor symptom (N; p < 0.0001) burden decreased, and autonomy for the activities of daily living (D; p = 0.005) improved. Conclusions: The MNCD classification could be useful to classify advanced PD patients and to monitor the response to a DAT.